2016
DOI: 10.1002/bjs.10084
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of negative-pressure wound therapy for closed surgical incisions

Abstract: BackgroundPostoperative wound complications are common following surgical procedures. Negative‐pressure wound therapy (NPWT) is well recognized for the management of open wounds and has been applied recently to closed surgical incisions. The evidence base to support this intervention is limited. The aim of this study was to assess whether NPWT reduces postoperative wound complications when applied to closed surgical incisions.MethodsThis was a systematic review and meta‐analysis of randomized clinical trials o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
175
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(195 citation statements)
references
References 43 publications
12
175
1
7
Order By: Relevance
“…Gillespie et al 96 conducted a pilot RCT to evaluate the utility of NPWT among 70 elective hip arthroplasty patients, demonstrating only a 3% reduction in SSI incidence. In a meta-analysis of NPWT use across an array of different surgical procedures, Hyldig et al 97 reported that the use of NPWT was associated with significant reduction in wound infection and seroma formation. Among high-risk patients, Stannard et al 98 conducted an RCT of 263 randomized patients with lower extremity fractures showing SSI reduction from 19% to 9.7% using NPWT.…”
Section: Wound Vacuum Dressingmentioning
confidence: 99%
“…Gillespie et al 96 conducted a pilot RCT to evaluate the utility of NPWT among 70 elective hip arthroplasty patients, demonstrating only a 3% reduction in SSI incidence. In a meta-analysis of NPWT use across an array of different surgical procedures, Hyldig et al 97 reported that the use of NPWT was associated with significant reduction in wound infection and seroma formation. Among high-risk patients, Stannard et al 98 conducted an RCT of 263 randomized patients with lower extremity fractures showing SSI reduction from 19% to 9.7% using NPWT.…”
Section: Wound Vacuum Dressingmentioning
confidence: 99%
“…The numbers needed to treat were 3 (seroma), 17 (dehiscence) and 25 (infection). Due to heterogeneity between the included studies, no general recommendations could be made yet[58]. However, this device has a potential for its use in immunosuppressed and obese patients undergoing KT.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In 2017, Willy et al published consensus recommendations for the use of CINPWT, describing patient characteristics, incisions, and operations with a high risk of developing surgical site infections and wound complications. 5,6 Today, specific indications for use of CINPWT continue to be defined. 4 However, even before these recommendations, CINPWT was widely used in multi-morbid patients undergoing major lower non-traumatic (above-ankle) amputation, although there was no evidence of this treatment.…”
Section: Introductionmentioning
confidence: 99%